2022
DOI: 10.52312/jdrs.2022.547
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of negative pressure wound therapy: Minimum five-year follow-up and review of the literature

Abstract: In the last decades, negative pressure wound therapy (NPWT) treatment has opened great possibilities in wound management. First used in the Russo-Afghan War in 1985 by Nail Bagaoutdinov, [1] modern vacuum treatment was, then, introduced by Louis Aregenta [1] and Michael Morykwas [1] in 1990 using a combination of polyurethane foam and a mechanical vacuum machine. [1] Use of the technique in everyday care began in 1993. In 2017, the textbook Negative Pressure Therapy: Theory and Practice was published in Hungar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Severe crush injuries and compartment syndrome are the most common reasons for amputation. [ 17 ] Early fasciotomy can prevent amputation, and our study reported a low rate of amputations, attributable to easy accessibility of our hospital and prompt fasciotomy. Rapid extrication and transport of patients to the nearest hospital by search and rescue teams are critical for early treatment of compartment syndrome and crush injury.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Severe crush injuries and compartment syndrome are the most common reasons for amputation. [ 17 ] Early fasciotomy can prevent amputation, and our study reported a low rate of amputations, attributable to easy accessibility of our hospital and prompt fasciotomy. Rapid extrication and transport of patients to the nearest hospital by search and rescue teams are critical for early treatment of compartment syndrome and crush injury.…”
Section: Discussionmentioning
confidence: 84%
“…The wound site was primarily followed by plastic surgeons and no infections were observed. [ 17 ] The most frequently performed surgery was debridement, which is a must to prevent infection and other complications. [ 10 , 17 - 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis by Jauregui et al,[ 5 ] including 23 studies of patients with post-fracture compartment syndrome and fasciotomy, the success rate of fasciotomy closure with dermatotraction method without the need for grafts was found to be 92% on average, while this success rate in VAC closure was 78%. In the study of Révész et al,[ 16 ] 81.6% of the grafts were needed after VAC. In our study, the graft was needed in 81.81% of the patients in the VAC group, while this rate decreased to 53.4% in the PDS group.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with major crush injury, there were more necrosis in the muscles. Therefore, the patients were treated with serial debridement, vacuum-assisted closure (VAC),[ 9 ] vascular repair, and antibiotic treatment. All the patients had deep muscle necrosis and, therefore, we did not consider exclusion of patients whose fasciotomy was completed.…”
Section: Methodsmentioning
confidence: 99%